2020
DOI: 10.1200/jco.2020.38.5_suppl.90
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence data (RWED) of financial toxicity (FT) in patients (pts) receiving cancer immunotherapy treatments.

Abstract: 90 Background: RWED denotes data accumulated via EHR as well as cutting edge technology paired with consumer mobile devices. We are reporting data on 105 pts, users of Belong.life, a worldwide mobile application, who received immunotherapy for their various cancers and were asked to reply to a short, targeted survey on their FT while on treatment. Methods: 105 pts anonymously and voluntarily replied to a survey which included 14 general information questions and those describing FT, its most common encountere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Monetary constraints can lead to “financial toxicity” (i.e., problems related to the cost of medical care) and add to the burden of cancer patients receiving treatment ( Oubre, 2019 ). Common reasons for financial distress are an uninsured status, high medical copayments or high drug and treatment copayments, loss of income, loss of coverage tied to work benefits, the need for medical leave or early retirement, or the uncertainty about how to navigate insurance coverage issues or safety-net resources ( Vorobiof et al, 2020 ; Rotter et al, 2019 ; Warsame et al, 2019 ). Given that financial hardship is associated with reductions in quality of life, adherence to treatment, and adverse psychological consequences, finances can become a source of harm to patients ( Rotter et al, 2019 ).…”
Section: Know Your Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monetary constraints can lead to “financial toxicity” (i.e., problems related to the cost of medical care) and add to the burden of cancer patients receiving treatment ( Oubre, 2019 ). Common reasons for financial distress are an uninsured status, high medical copayments or high drug and treatment copayments, loss of income, loss of coverage tied to work benefits, the need for medical leave or early retirement, or the uncertainty about how to navigate insurance coverage issues or safety-net resources ( Vorobiof et al, 2020 ; Rotter et al, 2019 ; Warsame et al, 2019 ). Given that financial hardship is associated with reductions in quality of life, adherence to treatment, and adverse psychological consequences, finances can become a source of harm to patients ( Rotter et al, 2019 ).…”
Section: Know Your Patientsmentioning
confidence: 99%
“…Some practices prefer to employ financial counselors or utilize the expertise of coders and payer experts to help patients navigate their benefits ( McGraill, 2019 ; Shah, 2019 ). Financial toxicity was reduced from 48% to 30% among surveyed patients receiving cancer immunotherapy after pretreatment financial counseling from their healthcare provider ( Vorobiof et al, 2020 ). Examples of brief conversations, including switching a patient's drug and other scenarios, demonstrate possible strategies for approaching cost conversations that could be adapted when discussing biosimilars ( Hunter et al, 2017 ).…”
Section: Know Your Patientsmentioning
confidence: 99%
“…Emotionale, soziale und finanzielle Auswirkungen (wie z. B. finanzielle Schwierigkeit [ 31 ], Isolation [ 23 ], Demoralisierung [ 14 ]) stellen relevante Bereiche dar, die bisher unzureichend adressiert werden und die ebenfalls bedeutende Aspekte innerhalb der „patient journey“ darstellen.…”
Section: Patientenzentrierte Lösungsansätze Im Gesamtablauf – Auf Das...unclassified
“…There is a significant body of recent literature examining the financial and social impact of a cancer diagnosis on patients and their families related to cancer treatment and follow-up care. These studies have shown impacts related to out-of-pocket costs (OOPC) [1–7], lost income for patients [8–14,15 ▪ ,16,17,18 ▪ ,19 ▪ ] or both [20–23,24 ▪ ,25,26,27 ▪ ,28–30]. In some cases, studies are focused on specific cancers including breast [4,18 ▪ ,22,23,31], colorectal [22,23,32,33], lung [22,23], prostate [3,22,23,25], other solid tumours [16,21,34] as well as hematologic malignancies [26].…”
Section: Recent Updates On Patients’ Financial Burden/toxicitymentioning
confidence: 99%
“…These studies have shown impacts related to out-of-pocket costs (OOPC) [1][2][3][4][5][6][7], lost income for patients [8-14,15 ,22,23,31], colorectal [22,23,32,33], lung [22,23], prostate [3,22,23,25], other solid tumours [16,21,34] as well as hematologic malignancies [26]. These data suggest that having metastatic disease [34], receiving immunotherapy treatment [30] and the specific tumour types [28] increases financial toxicity. A recent review by Longo et al [27 & ] illustrates that these costs continue to be of concern in a variety of countries, including: Canada, Australia, Ireland, UK, Germany, France, Denmark, the Netherlands, Finland, Malaysia and South Korea, despite largely public-funded healthcare systems.…”
Section: Introductionmentioning
confidence: 99%